Advances of radiolabeled GRPR ligands for PET/CT imaging of cancers - Yuze Ma; Feng Gao (Cancer Imaging, 2024)
Abstract GRPR is a type of seven-transmembrane G-protein coupled receptor that belongs to the bombesin protein receptor family. It is highly expressed in various cancers, including prostate cancer, breast cancer, lung cancer, gastrointestinal cancer, and so on. As a result, molecular imaging studies have been conducted using radiolabeled GRPR ligands for tumor diagnosis, as well as monitoring of recurrence and metastasis. In this paper, we provided a comprehensive overview of relevant literature from the past two decades, with a specific focus on the advancements made in radiolabeled GRPR ligands for imaging prostate cancer and breast cancer.